Identification and Characterization of ABA Receptors in Oryza sativa - He, Yuan; Hao, Qi; Li, Wenqi; Yan, Chuangye; Yan, Nieng; Yin, Ping (PLOS ONE, 2014)
Abscisic acid (ABA) is an essential phytohormone that regulates plant stress responses. ABA receptors in Arabidopsis thaliana (AtPYLs) have been extensively investigated by structural, biochemical, and in vivo studies. In contrast, relatively little is known about the ABA signal transduction cascade in rice. Besides, the diversities of AtPYLs manifest that the information accumulated in Arabidopsis cannot be simply adapted to rice. Thus, studies on rice ABA receptors are compulsory. By taking a bioinformatic approach, we identified twelve ABA receptor orthologs in Oryza sativa (japonica cultivar-group) (OsPYLs), named OsPYL1–12. We have successfully expressed and purified OsPYL1–3, 6 and 10–12 to homogeneity, tested the inhibitory effects on PP2C in Oryza sativa (OsPP2C), and measured their oligomerization states. OsPYL1–3 mainly exhibit as dimers and require ABA to inhibit PP2C’s activity. On the contrary, OsPYL6 retains in the monomer-dimer equilibrium state and OsPYL10–11 largely exist as monomers, and they all display an ABA-independent phosphatase inhibition manner. Interestingly, although OsPYL12 seems to be a dimer, it abrogates the phosphatase activity of PP2Cs in the absence of ABA. Toward a further understanding of OsPYLs on the ABA binding and PP2C inhibition, we determined the crystal structure of ABA-OsPYL2-OsPP2C06 complex. The bioinformatic, biochemical and structural analysis of ABA receptors in rice provide important foundations for designing rational ABA-analogues and breeding the stress-resistant rice for commercial agriculture.